Karakterisasi dan Evaluasi Plot Konservasi Ex Situ Merbau (Intsia Bijuga) di Bondowoso pada Umur 7 Tahun - Tri Pamungkas Yudohartono (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Merbau (Intsia bijuga) is a native species in Indonesia having high economic value of its timber Over exploitation of merbau timber have threatened its populations in natural distribution. Ex situ conservation plot of merbau was established at Sumberwringin Research Forest in Bondowoso, East Java. The objectives of this study are to know survival and growth characteristic of merbau from several provenances at Sumberwringin Research Forest at 7 years old. Genetic materias used in this study were orginated from Halmahera Timur, Waigo, Oransbari, Wasior, Nabire and Seram provenances. This plot test was designed as Randomized Complete Block Design The results showed that Wasior was provenance having the highest life percentage. Average life percentage of merbau at 7 years old was 78.26 %. It was indicated a good adapatability of merbau at ex situ conservation plot in Bondowoso. Average height was varied from 1.77 to 3.24 m with mean was 2.59 m. Average diameter was varied from 2.73 to 5.30 cm with mean was 4.37 cm. Genetic variation of height and diameter between provenances was significantly observed. The high genetic variation would increase selection opportunity to support tree improvement program.